Imagens, discursos visuais e pedagogia inaciana: contribuição à formação integral - Bezerra, Glaucia Valeria (Universidade do Vale do Rio dos Sinos, 2019)
This article aims to display the importance of the image and of the imagistic creation, from an urgent the student’s visual literacy that is integrally formed at the educational institutions of the Jesuit Network. With a qualitative approach, the exploratory and flexible research was made accordingly with bibliographic references. Therefore, the paper aims to stimulate the practice of the five dimensions of the Ignatian Pedagogy: contextualization, experience, reflection, action, and assessment, dialoguing with images in their visual discourses, matching methodologies and epistemological systems in the art field. Enjoying masterpieces and artifacts of the visual culture, the student produces and builds the imagistic repertoire to help his socioemotional cognitive development, with general autonomous critical and reflexive thinking. Thus, the images that flow in the social routine intersect the cultural universes and are established in the educational field. Therefore the involvement of the provocative teacher, mediator of the various contents of knowledge and the building of artistic, cultural and contextualized aesthetic information is stimulated to insert in the Jesuit Institutions the updating and the innovation of his proposals for integral education and formation
Keywords: Imagem; Criação imagética; Cultura Visual; Pedagogia Inaciana; Formação Integral; Image; Imagetic Creation; Visual Culture; Ignatian Pedagogy; Integral Formation; Visual Culture